2021
DOI: 10.12968/jowc.2021.30.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sensitivity, specificity and clinical utility of algorithms of spatial variation in sub-epidermal moisture (SEM) for the diagnosis of deep and early-stage pressure-induced tissue damage

Abstract: Background: Sub-epidermal moisture (SEM) is a measurable biomarker detecting early pressure damage in order to objectively support current ‘gold standard’ skin tissue assessments (STA) for the detection of deep and early-stage pressure-induced injuries or ulcers (PI/PUs). Objective: A multi-site, dual arm, cross sectional, retrospective study was conducted to evaluate the sensitivity, specificity and clinical utility of spatial variation in SEM readings between healthy and damaged skin tissue. Method: The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 41 publications
2
41
0
1
Order By: Relevance
“…Two values are displayed on the device's screen: an individual value for every single scan and the SEM Delta (∆SEM) score. The delta value is a measure of the difference in the SEM values between potentially damaged tissue and nearby healthy tissue [44,45]. Calculation of a 'delta' value compares multiple measurements within a specific anatomy, some of which will be healthy tissue, compensates for systemic changes, overcomes the limitation of inter and intra-patient variability (such as changes in the patient's hydration status), and provides a measure of tissue health condition [45].…”
Section: How the Device Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Two values are displayed on the device's screen: an individual value for every single scan and the SEM Delta (∆SEM) score. The delta value is a measure of the difference in the SEM values between potentially damaged tissue and nearby healthy tissue [44,45]. Calculation of a 'delta' value compares multiple measurements within a specific anatomy, some of which will be healthy tissue, compensates for systemic changes, overcomes the limitation of inter and intra-patient variability (such as changes in the patient's hydration status), and provides a measure of tissue health condition [45].…”
Section: How the Device Workmentioning
confidence: 99%
“…The delta value is a measure of the difference in the SEM values between potentially damaged tissue and nearby healthy tissue [44,45]. Calculation of a 'delta' value compares multiple measurements within a specific anatomy, some of which will be healthy tissue, compensates for systemic changes, overcomes the limitation of inter and intra-patient variability (such as changes in the patient's hydration status), and provides a measure of tissue health condition [45]. Clinical studies determined a threshold delta value of 0.6 as the cutoff so that a: a. Δ < 0.6 indicates a lower risk for a PI at the anatomic site, while; a, b. Δ ≥ 0.6 indicates an increased risk for PI at the anatomic site.…”
Section: How the Device Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Cause and effect level analysis at the patient demographic level was outside the scope of this study, particularly in light of other publications that address the characteristics of sub‐epidermal assessments made by the device at and around specific anatomies. Those studies show the device being neutral to patient skin tone and are unlikely to be adversely affected by patient‐specific factors, such as gender, race and comorbidities (Gershon & Okonkwo, 2021; Okonkwo et al, 2020). The authors are excited to continue researching SEM in combination with individual interventional modalities to determine their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…O'Brien et al, (2018) demonstrated that the device alerted HCPs to early and deep skin and tissue damage 4 days before damage was identified by visual skin assessment (VSA) with 100% specificity. Gershon and Okonkwo (2021) established the clinical significance of the SEM test in differentiating healthy and non‐visible damage under the skin before VSA for early and deep stage tissue damage. Okonkwo’s group demonstrated that the device alerted clinicians to tissue damage 4.74 days ± 2.39 days earlier than the diagnosis of a PI/PU by skin assessments with the diagnostic accuracy of the SEM test (SEM Scanner) exceeding clinical judgement alone in early and deep stage detection of developing PI/PUs at specific anatomies (Okonkwo et al, 2020).…”
Section: Chelsea and Westminster Hospital Nhs Foundation Trustmentioning
confidence: 99%